Hormonal induction of gonad maturation in female tinfoil barb fish (Barbonymus schwanenfeldii) using spawnprim hormone - Amalia Sutriana; Ahmad Baihaqi; Iwan Hasri; Nurliana; Hafizuddin Hafizuddin (Jurnal Akuakultur Indonesia)
The aim of this study was to analyze the effect of spawnprim hormone induction with different doses on gonadal maturity of tinfoil barb fish broodstock (Barbonymus schwanenfeldii). A completely randomized design (CRD) was used in this study with 4 treatments and 3 replications. Fish broodstock in group A (control) was not given any treatment, while fish broodstocks in groups B, C, and D were injected with spawnprim hormone at doses of 0.3 ml/kg body weight, 0.6 ml/kg body weight, and 0.9 ml/kg body weight, respectively. The measured parameters were gonad maturity level, broodstock weight gain, egg diameter, and fecundity. Data were analyzed using one way analysis of variance (ANOVA). The result showed that the gonad maturity level (GML) in groups B, C, and D (GML III and IV) was better than group A (GML I). Statistical analysis showed that the induction of spawnprim hormone on tinfoil barb broodstocks significantly affect (P<0.05) broodstock weight gain, egg diameter, and fecundity. The optimal dose of spawnprim hormone for tinfoil barb was 0.6 ml/kg body weight, with the average broodstock weight gain, egg diameter, and fecundity were 0.011 kg, 1.55 mm, and 102.15 eggs, respectively. The induction of spawnprim hormone has a positive effect on gonad maturation of tinfoil barb fish (B. schwanenfeldii), with the optimum dose is 0.6 ml/kg fish